Pengaruh Metode Contextual Teaching and Learning terhadap Kemampuan Pemecahan Masalah Matematika - Umayah Umayah; Arif Rahman Hakim; Arfatin Nurrahmah (JKPM (Jurnal Kajian Pendidikan Matematika), 2019)
The research conducted in SMP Al – Fathiyah Balekambang Kramat Jati Jakarta Timur has a purpose to know the influence of contextual teaching and learning methods on the ability to solve mathematical problems. The experimental research method with this post test only control group set the target population of all students enrolled at AL-Fathiyah Junior High School for the academic year 2018-2019. As for the affordable population in the study it limited only a grade VII student of 45 students. Sampling based on the population is affordable with multistage sampling technique in which it is a simple random sampling then purposive sampling. The instrument used is about the form of the description as many as nine items that have been validated empirically. The data analysis technique is done in a descriptive and inferential which is first conducted test analysis requirement in the form of test normality and homogeneity test. Based on the results of the hypothesis testing, this research can be concluded that there is a significant influence on contextual teaching and learning methods on mathematical problem solving skills